Kon: um pequeno stop motion em origami - Ohashi, Debora Akina [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Este presente trabalho remete sobre uma animação em estilo stop motion com base na arte oriental do origami. Explora-se a possibilidade de movimento do papel rígido com fotos. Um enredo original simples, uma raposa que explora um mundo infinito vazio. Ambiente minimalista, como cor base o branco e ocasionalmente outras cores.

This project is about a stop-motion animation based on the oriental art of origami.It explores the potential of rigid paper movement through photographs. The storyline is an original but simple one, featuring a fox that explores a boundless white world. The environment embraces minimalism, predominantly utilizing the color white, with occasional interjections of other colors.
Kon: a short stop motion with origami
Keywords: Origami; Design; Animação stop motion; Animation; Stop motion